Asuhan Keperawatan Maternitas dengan Post Sc: Intervensi Mobilisasi Dini (ROM) di RSUD Kajen - Indah Permata Sari; Nevi Sintarowati; Riski Agustina; R. Wahyuningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Sectio caesarean (SC) is a major surgical procedure performed to save the mother and baby when normal delivery is not possible. However, this procedure may cause postoperative complications such as impaired physical mobility due to pain, muscle weakness, and anesthesia effects. These limitations can delay the healing process, increase the risk of infection, and reduce the mother's self-care ability. One effective non-pharmacological intervention to accelerate recovery is early mobilization through Range of Motion (ROM) exercises. This case study aims to analyze the effectiveness of early mobilization (ROM) intervention on improving mobility and reducing pain in post-sectio caesarean mothers. The study was conducted in June 2025 at RSUD Kajen with three respondents who underwent SC for different obstetric indications (postterm, CPD, and severe preeclampsia). The research design used a descriptive case study with pre–post intervention approach. The results showed that after performing ROM exercises gradually from six hours post SC, pain intensity decreased from a scale of 7–8 to 1–3 within three days. Mobility ability improved from only being able to turn sideways to sitting and walking with assistance. Respondents also showed increased motivation and independence in self-care activities. In conclusion, early mobilization (ROM) intervention is effective in accelerating recovery for post-sectio caesarean mothers. This intervention helps reduce pain, improve circulation, strengthen muscles, and enhance psychological adaptation. Early mobilization should be applied as part of routine nursing interventions in the postpartum ward.